The Obstacles Of Applying The Total Educational Quality Standards At The University Of Science And Technology Of Yemen. "From The Perspectives Of Staff" - Al-Naggar, Noman Qaid; Abbas, Arif; Al Ameri, Abdh Qaid (University of Science and Technology, Yemen, 2015)
The aim of this study is to find out the obstacles of applying the total educational quality standards at the University of Science and Technology. It has been returned to previous studies and reviewed the obstacles in them, as well as it has been returned to the concepts of the total educational quality. Depending on these reviews, the obstacles from the perspectives of staff in five areas have been collected. The area of these obstacles are performance obstacles in the educational process, performance obstacles in the scientific research field, performance obstacles in community service, performance obstacles in the university administration, and obstacles associated with the organizational aspects. Such areas were organized in questionnaire.